2020
DOI: 10.1088/1742-6596/1691/1/012223
|View full text |Cite
|
Sign up to set email alerts
|

Modern trends in the digitalization of education

Abstract: The process of education digitalization has been on its way for a long time. However, a strong surge of interest arose during the period of temporary communication restrictions associated with Covid-19 and the widespread transition to a completely remote format of interaction between all participants in educational process. Digitalization has affected all levels of education and directly the activities of students, teachers, administrators, or stakeholders. The purpose of the study is to evaluate the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The studies conducted [4] have shown that the great variety of digital learning platforms, due to the specifics of different educational institutions, negatively affects the learning outcomes. It is therefore advisable to limit one educational institution to 3-5 platforms that are compatible and have a single access window.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies conducted [4] have shown that the great variety of digital learning platforms, due to the specifics of different educational institutions, negatively affects the learning outcomes. It is therefore advisable to limit one educational institution to 3-5 platforms that are compatible and have a single access window.…”
Section: Resultsmentioning
confidence: 99%
“…And from the beginning of 2020, the entire world, and the education sector in particular, have had to urgently search for and introduce alternatives to the full-time form of work. In education, one of them has been distance learning, which according to analysts' forecasts will be segmented in the following proportions by 2030 [4]: 55% for secondary education, 25% for higher education, 8% for pre-school education, 6% for corporate education, 8% for lifelong learning.…”
Section: Introductionmentioning
confidence: 99%
“…[12] see an urgent need for a new reform in the education sector to well prepare learners for the post-pandemic era [12]. However, the readiness of students who have completed online learning and its shortcomings are still unclear [13]. Thus, more research needs to be carried out for better explanation on the root causes that hinder the development of digitalization in higher education.…”
Section: A Digitalization In Education Contextmentioning
confidence: 99%
“…Russia acknowledges educational technologies as the new normal and has made them mandatory in education sector with the approval of distance learning system and the development of online corporate portals for teaching and learning [15]. Most educational institutions in Russia today have incorporated tablets, smartphones, and computers which resulted in physical activity reduction [13]. Meanwhile, a study in digital transformation in Africa found the privatization process has taken place in the national education sector where private sectors bring about educational technology solutions in the curricular, assessment, and school management [1].…”
Section: A Digitalization In Education Contextmentioning
confidence: 99%
“…Nonetheless, there was a notable spike in interest during the COVID-19-related temporary communication constraints and the general shift to an entirely remote structure of interaction amongst all participants in the educational process [6,7,8]. All educational levels and the actions of students, instructors, administrators, and other stakeholders have been directly impacted by digitalization [9,10]. Not only is digitalization a current trend [11,12], but it also presents a promising path for advancement in a number of areas, including education [13].…”
Section: Introductionmentioning
confidence: 99%